A study of the strength of glued laminated timber. Issue 4 (2nd October 2018) - Milner, H R
ABSTRACT: The paper presents methodologies for determining the bending strength of structural glued laminated timber (glulam) from lamination tension test strength data. The tension tests involve finger jointed bonded lamination pairs sampled to reflect manufacturer's practices of lamination stock purchases, defect removal and finger jointing while simultaneously taking account of knot, sloping grain and finger joint reinforcement as occurs within a glulam beam. It uses a modified Weibull weakest link theory with minimal extrapolation of the test data to determine beam strengths. The method is largely independent of any strength class system. The predictions are benchmarked against test data provided by Falk and values provided in European Standard EN14080.